Strategi Retorika Naratif Laporan Keberlanjutan Perusahaan Pertambangan - Lala Anggun Putri Wandira; Sri Pujiningsih (Universitas Muhammadiyah Malang, 2024)
Purpose: to explore sustainability disclosures based on GRI and identify the narrative rhetoric of sustainability reports in coal mining companies in Indonesia. Methodology/approach: content analysis method was used to identify 9 mining company sustainability reports during 3 years of observation. Data analysis through tracing the conformity of disclosures with GRI standards and identifying Aristotle's rhetoric, namely ethos, pathos and logos. Findings: (environmental disclosure indicators are the most reported and the logos narrative rhetoric strategy is the most used in coal mining companies' sustainability reports.Practical and Theoretical contribution/Originality: mining companies can use GRI and Aristotelian rhetorical strategies. This research enriches the study of narrative accounting from the perspective of Aristotle's rhetorical theory Research Limitation: the sample is limited to coal mining companies.